Identifikasi gejala psychotrauma pada remaja perempuan di lingkungan boarding school - Ainun Nikmah; Nandy Agustin Syakarofath (Cognicia, 2026)
Adolescence is a developmental stage vulnerable to psychological trauma, particularly in boarding school environments characterized byacademic pressure, strict discipline, and separation from family. This study aims to identify indications of psychotrauma symptoms amongfemale adolescents in a boarding school setting and analyze differences based on educational level. This descriptive quantitative studyinvolved 657 female students (aged 11–19) Junior and Senior High School, selected via convenience sampling. Psychotrauma symptomswere measured using the Indonesian version of the Global Psychotrauma Screen for Teens (GPS-T) and analyzed using JASP 0.95.4software. The results showed that the highest prevalence of symptomatic indications was anxiety (73.8%), followed by DSO (60.3%) & CPTSD (67.3%), while the lowest was substance abuse (6.7%). Significant differences were found based on educational level across most psychotrauma aspects (p < .001), except for self-harm and substance abuse. This study emphasizes the urgency of preventive interventions based on emotion regulation and stress management in schools. School management is advised to implement trauma-informed care and developmental-sensitive counseling services to optimize student’s self-concept and interpersonal relationships, particularly at the early educational level.